The Meaning Of Pre Marriage Counseling In Marriage Law In Indonesia - kasiani, kasiani; Ervika Dewi , Wahyuni (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
This study explores the importance of premarital counseling in the context of Indonesian marriage law, with a focus on preparing prospective couples for a happy and healthy married life. Using a qualitative phenomenological approach, data was collected through in-depth interviews with couples who had participated in premarital counseling. The results showed that premarital counseling plays an important role in equipping couples with knowledge about effective communication, conflict management, reproductive health, and rights and obligations in marriage. This finding is supported by previous research that shows a positive relationship between premarital readiness and long-term marital success. The mentorship program is based on a strong legal framework, including Law No. 1/1974 on Marriage and Minister of Religious Affairs Regulation No. 20/2019. However, the implementation of premarital guidance faces challenges, such as limited facilities and manpower at the Office of Religious Affairs (KUA) and differences in the quality of the program across regions. In addition, cultural and social barriers affect the acceptance and effectiveness of this guidance. This study emphasizes the importance of adjusting the guidance program to better consider local customs and culture. Thus, premarital guidance is expected to reduce divorce rates and improve the quality of marriages by preparing prospective couples for the challenges of married life. The findings provide important insights for policy makers and practitioners to improve the quality and accessibility of premarital guidance in Indonesia.